Reposisi Guru Pendidikan Agama Islam di Era Generative Artificial Intelligence: Penguatan Peran Humanistik dalam Pembelajaran - Nur Azizah; Firza Al-Khoiri; Mhd Khairi Azhar; Gilang Irhamsyah; Bagus Jordan (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
The rapid development of Generative Artificial Intelligence (AI) has transformed learning practices, requiring Islamic Religious Education (PAI) teachers to redefine their professional roles beyond knowledge transmission. While AI expands access to learning resources and supports instructional efficiency, it also raises concerns regarding digital ethics, the validity of religious information, declining educational interaction, and the erosion of teachers' epistemic authority. This study examines the repositioning of PAI teachers in the era of Generative AI by identifying emerging challenges and exploring strategies that reinforce their humanistic role in learning. Employing a qualitative library research approach, the study analyzed scholarly books, journal articles, and relevant academic documents through content analysis. The findings reveal that the role of PAI teachers is evolving into that of learning facilitators, knowledge curators, digital ethics guides, and mentors of character and spirituality. These human-centered roles remain indispensable because moral exemplification, spiritual guidance, and meaningful interpersonal interaction cannot be replicated by AI systems. Furthermore, the study emphasizes the importance of strengthening teachers' digital competence, fostering critical thinking, integrating AI responsibly into educational practices, and reinforcing Islamic values throughout the learning process. Ultimately, rather than replacing teachers, Generative AI reinforces the indispensable humanistic mission of PAI teachers in cultivating knowledgeable, ethical, and spiritually grounded learners.